Specificities of the public of literary festivals in the segment of cultural events - Liberato, Pedro (2019)
This article aims to contribute to the deepening of scientific knowledge about the specificities of the public of literary festivals in the segment of cultural events. The objectives of this research are: Identify and ascertain how the sociodemographic characteristics of participants in literary festivals relate to their motivations with the event and verify the existence of a market niche faithful to literary events. To achieve the defined objectives, 226 validated questionnaires were gathered from participants in the literary festival "Correntes d'Escritas, 2018", held in the city of Póvoa de Varzim, between February 21 and 24, 2018. The main findings of the study confirm the hypotheses associated with the objectives presented. These finding indicate that this audience is very satisfied with the organization of the event and with the event in general, they highlight the cultural dimension of the experience and intend to return and recommend the event. The results obtained constitute an important instrument to raise awareness of the entities responsible for the organization of literary events, not only of the event "Correntes d'Escritas" but also of other similar events, for the adjustment of the design, planning and coordination of these events according to the specificities of this public, resulting in greater benefits for the regions involved.